Pengaruh Kualitas Layanan IBS Mobile terhadap Kepuasan Anggota KSP-PS BMT Artha Buana Metro - Nurhayati, Putri; Mukhlisin, Ahmad; Farida, Annikmah; Arifin, Zainal; Nafisah, Jauharotun (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
Along with the development of Islamic banking and Islamic financial institutions, both rural banks and cooperatives ind Indonesia today, the quality of services is an important factor in competitiveness. This happens because banking is a sharia-based service provider. Currently, there are many services provided by bank and non-bank financial institutions to make it easier for custimers to carry out their transaction activities. With the development of sophisticated technologu, it is now easier for customers to make transactions using electronic media without direct contact. This article aims to determine the effect of IBS Mobile on member satifaction at BMT Artha Buana Metro. Data obtained from questionnaires that have been answeres by respondents, namely a simple liner regression. R-Squared of 80,70 % shows that the independent variables not included in this study. Thus the results of the studi indicate that the quality of IBS Mobile services has an effect on the satisfaction of BMT Artha Metro members.